Strategies and techniques for creating educational programs for teachers of natural science subjects - Nurmukhamedova, Zhanara; Nurbayeva, Dilara; Yerzhenbek, Bulbul; Nassirova, Diana (International Journal of Evaluation and Research in Education (IJERE), 2025)
The relevance of the study is based on the current educational reforms in the Republic of Kazakhstan, which is implemented under the conditions of humanization and integration at different levels. This is based on the development of the informatization and technologization of current science and practice, the trend towards the interpenetration of certain fields of knowledge into others, the exploration of interdisciplinary approaches in explaining the current world view, which is itself multidimensional, persistent, impartial and integrative. The purpose of this study is to provide a theoretical framework, developing a model for the training of modern natural science teachers and investigate the main stages of curriculum development for future teachers. The objectives of the study are aimed at disseminating knowledge about the development of effective educational programs. Objective methods included theoretical analysis, analysis of future teachers’ activities, synthesis of philosophical and educational psychology literature, modelling and observation. The study investigated and systematized approaches to the methodological design of educational programs and identified all types of professional competence using the method of analysis.